New Pentecostal churches, politics and the everyday life of university students at the University of Zimbabwe - Gukurume, Simbarashe (Department of Sociology, 2019)
In the past 15 years, there has been a concerted ‘Pentecostalisation’ of university spaces in Africa. Despite enormous growth in Pentecostal Charismatic Church membership and activities on African university campuses, and its attendant implications for academic and everyday life, there is hardly any study that explores this phenomenon. Thus, little is known about the complex entanglements between religion, politics and the dynamics of the everyday within the university campus and how this mediates students’ subjectivities. This thesis examines the lived experiences and everyday lives of university students at the University of Zimbabwe (UZ). The thesis is based on the narratives of students drawn through a qualitative methodology and more particularly, through participant observation, semi-structured and in-depth interviews over 15 months. Findings in this study revealed that university students convert and sign-up for new Pentecostal Charismatic Churches (PCCs) because they were imagined as spaces through which young people could forge supportive economic and social networks. PCCs’ gospel of prosperity and ‘spiritual warfare’ technologies were also deeply attractive to students who were caught in the hopelessness and uncertainty wrought by the country’s protracted socio-economic and political crisis. In this context, PCCs cultivate a sense of hope and optimism. However, although new PCCs reconfigure young people’s orientation to the future, many PCC promises remain elusive. The entrance of PCCs onto this university campus has also lead to institutional conflict as new churches struggle against the entrenched historical privilege of mainline churches- and the political influence of their followers in university management. New PCCs on the UZ campus have also become heavily involved in student and national politics, which further complicates their relationship with the university and the state. This thesis demonstrate the extent to which faith permeates every aspect of university experience for those who subscribe to its Pentecostal forms. I argue in this thesis that these complex linkages between faith and university life are mediated by the wider politics of the country, including linkages between the state and the university.